Effect of Processing Treatment of Pineapple Leaf Fiber (PLF) with Liquid Smoke on Tensile Properties and Impact of Pineapple Fiber Reinforced Composites - Mukhlis Muslimin; Kifli Umar; Sandi Rais; Raulia Taib (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Research objectives to determine the effect of treating pineapple leaf fiber (PLF) with liquid smoke on the tensile toughness of composites and the impact strength of pineapple leaf fiber (PLF) reinforcement. The Method of immersing the fiber with liquid smoke was done in 1, 2, and 3 hours, then heating it in the oven at 40⁰c for 30 minutes. A tensile and impact test specimen following the ASTM D638 – Type IV standard and ASTM D5942 standard. The tensile strength of the composite at 1 hour of treatment was 64.42 MPa; at 2 hours, it increased by 72.53 MPa, and at 3 hours, it increased again by 74.65 MPa. In the composite impact test with fiber reinforcement, the 1-hour treatment was 9.32 J/m², the 2-hour treatment increased by 13.44 J/m², and the 3-hour immersion decreased by 10.21 J/m². The effect of liquid smoke treatment processing on PLF on the tensile strength and impact toughness of the composites shows that the PLF reinforcing composite experienced the most significant change in tensile strength at 3 hours of treatment, and impact toughness occurred at 2 hours of treatment; this shows that liquid smoke can change the strength of PLF to be stronger and tougher.